Kinematic analysis of resist-and-release sprint running - Nemtsev, O.; Nemtseva, N. (ISBS Proceedings Archive (Michigan), 2017)
The objective of this study was to compare the kinematic characteristics of athlete's movements at the resistance and release phases of resist-and-release sprint running and free maximal sprint running. Five female sprinters and heptathletes and three male sprinters took part in the study. Videotaping was done at 240 Hz. 2D video analysis was performed using SkillSpector software. It was found that horizontal takeoff velocity, step length, ground contact time, knee angle at touchdown and trunk tilt at touchdown and takeoff had significant differences between release and resistance phases of resist-andrelease sprint running, along with constant speed phase of free sprint running. Most studied characteristics were the same in both the release phase of resist-and-release sprint running and in the acceleration phase of free sprint running.